Kangaroos - Duling, Kaitlyn (Minneapolis, MN : Bellwether Media, 2021)
Relevant images match informative text in this introduction to kangaroos. Intended for students in kindergarten through third grade.
Includes bibliographical references (page 23) and index.
2.6
K-3
520L
L
Keywords: Red kangaroo -- Juvenile literature; Kangaroos -- Juvenile literature; Red kangaroo; Kangaroos; Grassland animals; Marsupials; Animals; Readers (Elementary)